The Smartphone Pandemic: How Big Tech and public health authorities partner in the digital response to Covid-19. Issue 8 (2nd September 2021) - Storeng, Katerini Tagmatarchi; de Bengy Puyvallée, Antoine
ABSTRACT: Digital technologies harnessed through smartphones have been deployed widely to support the response to Covid-19 internationally, often through partnerships between 'Big tech' and telecoms corporations and public health authorities. This paper provides an overview and critical analysis of the rapid rise of such new forms of public-private cooperation, focusing on their manifestation in the European region in the first phase of the pandemic. Drawing on a review of international media and documents, we discuss three main domains of public health action in which private technology companies and public health authorities have converged: contact-tracing, epidemic modelling and public health communication to manage the 'infodemic' of misinformation about the new coronavirus. Critics have raised concerns about how the digital response to Covid-19 may threaten privacy and enable greater state surveillance and control, and the possibility that semi-automated decision-making may exacerbate existing discrimination and inequalities. Our analysis extends such critiques by considering what the digital response to Covid-19 reveals about tech corporations' growing power to influence public health agendas. We discuss how they promote technical solutions to public health challenges that are politically seductive, but that have uncertain effectiveness and societal implications that warrant critical scrutiny.